ChemInform Abstract: Metal‐Free Oxidative Hydroxyalkylarylation of Activated Alkenes by Direct sp3 C—H Functionalization of Alcohols. Issue 51 (17th December 2013) - Meng, Yuan; Guo, Li‐Na; Wang, Hua; Duan, Xin‐Hua
Abstract A variety of substituted oxindoles is synthesized by a tandem radical addition/cyclization reaction of corresponding acrylamides with different alcohols.